IFNGR1 gene promoter polymorphisms and susceptibility to cerebral malaria. - Koch, O; Awomoyi, A; Usen, S; Jallow, M; Richardson, A; Hull, J; Pinder, M; Newport, M; Kwiatkowski, D (2002)
Interferon (IFN)-gamma is a critical mediator of immunity to malaria. This study explored the relationship between polymorphisms in the promoter region of the gene encoding IFN-gamma receptor 1 (IFNGR1) and susceptibility to malaria in African children. Four polymorphisms were found in the region between -1400 and +100 nt of the translational start site by sequencing, and analysis of 562 nuclear families revealed 6 haplotypes. Case-control analysis of 562 Gambian children with severe malaria and 569 umbilical cord blood samples (controls) showed that in Mandinka, the major Gambian ethnic group, heterozygotes for the IFNGR1-56 polymorphism were protected against cerebral malaria (odds ratio, 0.54; P=.016) and against death resulting from cerebral malaria (odds ratio, 0.22; P=.006). Analysis of a family study by transmission disequilibrium testing revealed a similar result. Further data are needed to validate this finding, but these results are reminiscent of those for other well-established heterozygote advantages, such as that associated with hemoglobin S.